THE RELATIONSHIP BETWEEN TEACHERS’ KNOWLEDGE, ATTITUDE AND PRACTICES TOWARDS LEARNING DISABILITIES OF THE STUDENTS - S. RAJKUMARI (The Journal of Research ANGRAU, 2023)
The research was conducted with the aim of understanding the relationship between teachers’ knowledge, attitude, and practice towards learning disabilities of the students. For this study, 133 primary school teachers were chosen at random in 2022. The information on primary school teachers’ Knowledge, Attitude, and Practices (KAP) was collected by a KAP scale developed by the researcher. The scale wasvalidated and verified for reliability using Cronbach’s Alpha. The reliability score of the constructed KAP scale was 0.829, 0.854, and 0.700 correspondingly suggesting good reliability. Results showed that more than half of teachers (69.2%) had a moderate degree of knowledge and 54.9% were found to have a neutral attitude towards learning disability of the students. In terms of practices, a good level of practicesamong nealry three-fourth(72.9%) of the teachers was noted. A significant association was recorded between the knowledge and attitude of primary school teachers towards learning disabilitiesof the students. However, the results did not record practices being significantly interrelated to the knowledge and attitude towards learning disabilities of the students among primary school teachers, implying that knowledge or attitude might not influence practices as the practices remains self-regulated.